EFEKTIVITAS ARANG AKTIF CANGKANG KEMIRI (Aleuritas molaccanu) UNTUK PENGOLAHAN LIMBAH TEMPE - Bryan Fery; Charles Situmorang; Ai Silmi (JURNAL TECHLINK, 2022)
This study aims to determine the effect of giving candlenut shell activated charcoal using the parameters BOD (Biochemical Oxygen Demand), TSS (Total Suspended Solid), and pH (power of hydrogen) in tempe waste. The research uses quantitative methods, the type of research is experimental and laboratory observation. The research sample consisted of tempe waste and candlenut shell activatedcharcoal. The data analysis technique consisted of calculating the effectiveness and efficiency of removal, as well as the Kruskal-Wallis statistical test. The results showed that activated charcoal of candlenut shells could reduce BOD and TSS levels in tempe waste. In addition, it can increase the pH of tempe wastewater to normal (pH = 7). Overall, the BOD parameters are still in normal conditionsand have not passed the predetermined threshold. The removal efficiency of activated charcoal from candlenut shells on BOD, TSS, and pH levels in tempe waste as a whole increased. The results of the Kruskal-Wallis H test for the BOD parameter obtained a significant value (Asymp. Sig.) of 0.083 > 0.05. TSS obtained a significant value (Asymp. Sig.) of 0.881 > 0.05. pH obtained a significant value (Asymp. Sig.) of 0.351 > 0.05. Thus, H0 is accepted or there is no significant (significant) difference in the ability of candlenut shell activated charcoal to BOD, TSS, and pH levels in tempe waste. This is because the samples used in laboratory tests on tempeh waste are still small, only repeated twice, the weight of the candlenut shell activated charcoal is only 5 grams and 10 grams, respectively.The conclusion shows that there is a decrease caused by giving candlenut shell activated charcoal using BOD (Biochemical Oxygen Demand) and TSS (Total Suspended Solid) parameters, as well as making the pH (power of hydrogen) neutral (pH 7) in tempe waste.